1 - Introduction: Student Activism, Structural Adjustment and the Democratic Transition in Africa - Zeilig, Leo; Dawson, Marcelle (Journal of Higher Education in Africa, 2008)
University students in the period following independence were a transitory social group, who held well-founded expectations of rewarding and high-status employ- ment after graduation. In the 1970s many of these assurances began to erode as countries that had attempted to implement state-led development faced interna- tional recession and internal corruption and decay. State funding of higher educa- tion by the late 1970s was being targeted for restructuring by the World Bank and the International Monetary Fund (IMF). Student activism was affected: while stu- dents clung onto a self-conscious elitism, the reality of student poverty and the financial crises of African universities transformed their activism. As well as see- ing their status as a privileged group collapse, there was an unprecedented ‘con- vergence of forces’ between students and the popular classes. This introduction surveys the role of students, the nature of their protest and their relationship with civil society in the processes that brought about a wave of multi-party elections and democratic struggles in Africa. The article critically intervenes in some of the most important debates on the role of student activism on the continent and intro- duces the contributions in this special issue devoted to student activism.